Ответы 1

  • х-((х-(х*1/3+0,8))*6/7)+2=4х-((х-(х*1/3+0,8))*6/7)=4-2х-((х-(х*1/3+0,8))*6/7)=2х-(х-(х*1/3+0,8))*6/7=2х-6/7х-6/7(х*1/3+0,8)=21/7х-6/7х-6*0,8/7=2-5/7х-4,8/7=2-5/7х-48/70=2-5/7х-24/35=2-5/7х=2+24/35-5/7х=2 24/35-5/7х=94/35х=-94/35:5/7=-97/35*7/5=-97/5*1/5=-97/25=-3 22/25
    • Автор:

      houdini
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years